2018
DOI: 10.1016/j.simyco.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of fungal diversity in a mosaic landscape in Germany

Abstract: This study aims at characterizing the diversity and temporal changes of species richness and composition of fungi in an ecotone of a forest border and a meadow in the Taunus mountain range in Germany. All macroscopically visible, epigeous fungi and vascular plants were sampled monthly over three years, together with climatic variables like humidity and temperature that influence fungal diversity and composition as shown by previous studies. In this mosaic landscape, a total of 855 fungal species were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…It suggests that in a given area, the ratio of species richness of fungi to species richness of vascular plants is about 6:1. This fungus to plant species ratio has been roughly confirmed by Rudolph et al ( 2018 ) through species inventories using traditional methods. Recent data obtained by environmental sequencing, however, has shown that 6:1 is rather conservative and probably overlooks diversity of fungi revealed by molecular methods (Hawksworth and Lücking 2017 ; see also discussion).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…It suggests that in a given area, the ratio of species richness of fungi to species richness of vascular plants is about 6:1. This fungus to plant species ratio has been roughly confirmed by Rudolph et al ( 2018 ) through species inventories using traditional methods. Recent data obtained by environmental sequencing, however, has shown that 6:1 is rather conservative and probably overlooks diversity of fungi revealed by molecular methods (Hawksworth and Lücking 2017 ; see also discussion).…”
Section: Introductionsupporting
confidence: 61%
“…If mycologists working in the field in West Africa could be trained to consider fungi of any group (macro- and microfungi, lichens), and if they would include morphospecies, the numbers would be much higher (cfr. Rudolph et al 2018 ). This incomplete knowledge results in saturation curves showing slight and premature tendencies to saturation and in an underestimation of species richness by statistical estimators.…”
Section: Discussionmentioning
confidence: 99%
“…Variation at shorter time‐scales is often in line with the normal biological responses of the pest to environmental or seasonal variation, such as temperature, day length or rainfall, or in response to seasonal variation in host quality (Jumpponen & Jones, ; O'Hanlon, ; Rudolph, Marciá‐Vincente, Lotz‐Winter, Schleuning, & Piepenbring, ; Voříšková, Brabcová, Cajthami, & Baldrian, ; Wolda, ). For instance, insects that feed on the leaves of deciduous trees will be less abundant in autumn, when their main food source is scarce.…”
Section: Factors Affecting Species Occurrence and Diversitymentioning
confidence: 92%
“…Kebanyakan jamur hidup pada habitat lembab. Jamur dapat menggunakan tanah, kayu, daun, dan bahkan bebatuan sebagai substrat tumbuhnya (Rudolph, Maciá-Vicente, Lotz-Winter, Schleuning, & Piepenbring, 2018). Seperti penelitian sebelumnya yang dilakukan oleh Purwanto et al, 2017 dan Nasution, Rahayu Prasetyaningsih, & Ikhwan, 2018 yang menyatakan bahwa keanekaragaman jenis jamur makroskopis yang terdapat dihutan ditentukan oleh kondisi habitat tempat tumbuh jamur.…”
Section: Pendahuluanunclassified